Behavior of highly-siderophile elements during magma degassing: A case study at the Kudryavy volcano - Yudovskaya, M.; Tessalina, Svetlana; Distler, V.; Chaplygin, I.; Chugaev, A.; Dikov, Y. (Elsevier Science BV, 2008)
The capacity of natural vapor phase to transport metallic elements is not unambiguously established relative to that of a liquid hydrothermal phase. We measured highly-siderophile element (HSE) and Au abundances in gas condensates and mineralized rocks in order to examine the geochemical behavior of these elements during magma degassing at the Kudryavy volcano, Kurile Arc. Gas condensates of the Kudryavy volcano are enriched with Re, Os and Au (to 210 ppb Re, 0.907 ppb Os, 2.4 ppb Au, 0.49 ppb Pt, 0.4 ppb Pd, 0.04 ppb Ir, 0.07 ppb Rh, 0.009 ppb Ru). The measured enrichment factors demonstrate that Os is the element that is most strongly compatible with fluid. Fluid compatibility decreases in the sequence: OsNReNAuNPtNPd over the temperature range from 480 to 850 °C. The mobility of HSE and Au in fluid is confirmed by the sublimation of their compounds, amongst which rheniite ReS2 and K perrhenate KReO4, native Pt, Pt–Pd selenide and various Au alloys have been identified with a scanning electron microscope [Nature 369 (1994) 51; Miner. Deposita 40 (2006) 828]. In addition, new HSE compounds, including ReO2, ReO3, Pt(OH)2 and metal-chloro-organic complexes, were detected in the sublimates using X-ray photoelectron spectroscopy. In contrast to the chalcophile behavior of Pb, Re and Os exhibit a dual behavior in the gaseous phase, since both sulfide and oxide phases containing these metals precipitate throughout the entire temperature range. However, available mineralogical, experimental and thermodynamic modeling data indicate that Re and Os are preferentially transported as oxygen-bearing species. Data on metal contents in fumarolic crusts of the volcano confirm that a high-temperature low-density fluid can concentrate these metals to economic grade.Newly obtained data on the Pb and Sm–Nd isotopic composition of volcanic gas condensates and host rocks were correlated with available data on Re and Os abundances and with the Re–Os isotopic composition of the same sample set in order to identify the possible sources of the magmatic melts. The homogeneity of the Pb and Nd isotopic composition of volcanic rocks (206Pb/204Pb: 18.33–18.41, 207Pb/204Pb: 15.52–15.54, 206Pb/204Pb: 38.19–38.24; n=6; 143Nd/144Nd: 0.513067–0.513118; n=5)indicates that the main source of the melts was metasomatised depleted MORB mantle. This is consistent with the relatively low radiogenic 187Os/188Os isotope ratios of younger basaltic andesites and fumarolic gas condensates, but is inconsistent with theradiogenic Os isotope characteristics of the acid volcanic rocks and the high Re abundance in rocks and fluids [Geochem. Cosmochem. Acta 72 (2008) 889].The results of this study suggest that similar elemental and isotope HSE signature can be characteristic of HSE fractionation in other environments of low-density oxidizing fluid stability.